PENGARUH PEMEBERIAN SUSU KEDELAI (GLYCINE MAX MERRIL) TERHADAP PENINGKATAN PRODUKSI ASI IBU MENYUSUI 0-6 BULAN DI PMB SURYANI KECAMATAN MEDAN JOHOR TAHUN 2019 - Putri Ardiana Rizki; Evi Irianti; Betty Mangkuji; suswati M. Kes (Poltekkes Kemenkes Medan, 2020)
Introduction: Breastfeeding from day one is not always easy because many mothers face problems doing it. The events that often occur on the first day of breastfeeding are the difficulty of milking out or the production of slightly mother's milk and the baby will not suck. It makes mothers think that their baby will not get enough milk so mothers often take steps to stop breastfeeding and replace it with formula milk. Methods: This study used a Quasi Experiment with a pretest and posttest design approach, with a population of all breastfeeding mothers of 0-6 Months in Suryani midwifery clinic of Medan Johor sub district as many as 52 people. The sample in this study used a purposive sampling technique of 30 respondents. Resulits and Discussion: The results of this study indicate there are differences in baby's weight before the intervention and after the intervention with p value = 0,000 <? (0.05) where an increase in baby's weight was 350 grams. Consclusion: The conclusion of this study there is the effect of giving soybean milk to increase milk production in breastfeeding mothers of 0-6 months in Suryani midwifery clinic of Medan Johor sub district in 2019 so it is expected that health workers, especially midwives, can provide counseling to pregnant women in order to be able to cultivate soybeans so that they can used as an alternative for breastfeeding.